2009
DOI: 10.1093/hmg/ddp459
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association of FOXO1A and FOXO3A with longevity trait in Han Chinese populations

Abstract: FOXO1A and FOXO3A are two members of the FoxO family. FOXO3A has recently been linked to human longevity in Japanese, German and Italian populations. Here we tested the genetic contribution of FOXO1A and FOXO3A to the longevity phenotype in Han Chinese population. Six tagging SNPs from FOXO1A and FOXO3A were selected and genotyped in 1817 centenarians and younger individuals. Two SNPs of FOXO1A were found to be associated with longevity in women (P = 0.01-0.005), whereas all three SNPs of FOXO3A were associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
222
2
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 275 publications
(232 citation statements)
references
References 63 publications
3
222
2
5
Order By: Relevance
“…(2009) analyzed six SNPs from FOXO1A and FOXO3A genes by comparing 761 centenarians and 1056 younger individuals (control group) of the Han Chinese population. They found two SNPs of FOXO1A to be negatively associated with longevity in women, rs2755209 and rs2755213.…”
Section: Population Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…(2009) analyzed six SNPs from FOXO1A and FOXO3A genes by comparing 761 centenarians and 1056 younger individuals (control group) of the Han Chinese population. They found two SNPs of FOXO1A to be negatively associated with longevity in women, rs2755209 and rs2755213.…”
Section: Population Studiesmentioning
confidence: 99%
“…They found two SNPs of FOXO1A to be negatively associated with longevity in women, rs2755209 and rs2755213. On the other hand, all three SNPs studied for FOXO3A (rs2253310, rs2802292, and rs4946936) were positively associated with longevity in both genders (Li et al ., 2009). They have concluded that as FOXO1A is more strictly associated with human female longevity, the genetic contribution to longevity trait may be affected by genders (Li et al ., 2009).…”
Section: Population Studiesmentioning
confidence: 99%
“…However, two loci that are repeatedly found by GWAS of aging are APOE (Deelen et al, 2011; Ewbank, 2007; Gerdes, Jeune, Ranberg, Nybo, & Vaupel, 2000) and FOXO3A (Anselmi et al, 2009; Flachsbart et al, 2009; Li et al, 2009; Pawlikowska et al, 2009; Willcox et al, 2008). Similar to AD, APOE ε2 is found to be enriched in elderly and centenarians compared to younger individuals (Seripa et al, 2006).…”
Section: Molecular Links Between Aging and Admentioning
confidence: 99%
“…In invertebrates, FOXO transcription factors are important for longevity downstream of insulin signaling (Lin et al, 1997;Ogg et al, 1997;Giannakou et al, 2004;Hwangbo et al, 2004). Interestingly, polymorphisms in the FOXO3 gene are associated with extreme longevity in humans (Anselmi et al, 2009;Flachsbart et al, 2009;Li et al, 2009;Pawlikowska et al, 2009). In adult HSCs and NSCs, FOXO factors cooperate to regulate stem cell selfrenewal and homeostasis.…”
Section: Foxo Transcription Factors In Adult Stem Cells: Integrating mentioning
confidence: 99%